Lymfatické metastazování očima patologa - Němejcová, K; Dundr, P (Rozhledy v chirurgii, 2014)
Metastasis of malignant tumors into the lymph nodes is one of the basic types of tumor spread occurring particularly in carcinomas, but also in some sarcomas. Examination of lymph nodes is a crucial part of surgical staging and influences the prognosis and treatment of the patient. The following text discusses the general mechanisms of metastasis and methods of processing and the examination of lymph nodes, including the sentinel lymph node concept.
Keywords: lymfatické uzliny; Lymphatic Metastasis; lymfatické metastázy; Lymph Nodes; Humans; biopsie sentinelové lymfatické uzliny; Sentinel Lymph Node Biopsy; lidé